Assessment of Health Problems for the Elderly at the Nursing Home in Baghdad city - Abdul Mohsin, mohammed; AL. Janabi, Nahida; Al - Naqeeb, Abdul Khaleq (Iraqi National Journal of Nursing Specialties, 2012)
Objective: Assessment of health problems and identify demographical information to elderly. Methodology: it is a descriptive study, data were collected by the researchers depended on the direct interview with the elderly by using the study instrument (questionnaire) as well as review the records of the geriatric. Results: The majority of study sample (66%) were males and (24.3%) were within age group (70-74) years, (44.7%) were widows, and (41.7%) did not read and write. This study applied the international classification of diseases(short-table) in (11) items, which stated that most of the elderly were complaining from health problems: debility of hearing (80.65%), eczema or allergies (69.35%), debility of vision (66.92%), difficulty breathing (65.56%), loss of teeth (56.7%), chronic arthritis (54.55%), chronic headache (51.75%), anemia (51.56%), chronic constipation (46.36%), heart failure (30.43%), and retention of urine (30.19%). Recommendations: There must be a doctor with diseases of ageing presented at Nursing home and nursing staff commensurate with the number of elderly.